Radiometric Measurements in of Japanese barberry (Berberis thunbergii DC.), Boxwood (Buxus sempervirens L.) and Gold tassel (Euonymus japonica Thunb.) Under Cadmium and Zinc Stress - Turfan, Nezahat; Genç, Erkan (Kastamonu Üniversitesi, 2022)
In this study, the effects of Cd and Zn applications on the activity concentration and transfer factors in the Japanaesebarberry, Boxwood, and Gold tassel leaves were investigated using gamma-ray spectrometry. The mean concentrations (in Bq kg-1) of radionuclides in the studied soil samples were found to be 289.40±32.47 for 238U, 241.76±27.47 for 232Th, 783.63±83.46 for 40K, and 31.44±5.63 for R 137Cs while the respective values in the studied species were 168.6±20.1- 288.8±34.5, 145.9±19.1-250.3±32.4, 434.6±52.2-828.4±99.4, and 16.1±1.8-28.3±3.3. The activity concentrations were found to be at the lowest in the control group and 400 µM Zn for all three species, and at the highest level at 25 µM Cd in general in the species. The order of radionuclides by the highest activity concentrations was 40K>238Uz232Th>137C, whereas the order of species was Gold tassel>Boxwood>Japanaese barberry. TF (232U, 232Th, 40K, and 137Cs) values were found to be between 0.583 and 0.998, between 0.604 and 1.036, between 0.555 and 1.057, and between 0.513 and 0.899. And also, while the order of species by the activity concentration was Gold tassel>Boxwood>Japanaese barberry the order of species by the TF values was Boxwood>Gold tassel>Japanaese barberry. In conclusion, plants’ radionuclide activity concentrations were found to be at the highest level in 25 µM Cd group and at the lowest level in the control group. Considering all the data, it can be stated that a low dose of Cd was effective on the radioactivity concentrations and Gold tassel could be used as the indicator plant in radiation pollution.
Keywords: Engineering; Mühendislik; Cadmium; Zinc; Radioactivity; Transfer factor